2016
DOI: 10.4238/gmr15048775
|View full text |Cite
|
Sign up to set email alerts
|

CD40 functional gene polymorphisms and mRNA expression in rheumatoid arthritis patients from western Mexico

Abstract: ABSTRACT. The CD40 pathway is involved in the development and pathogenesis of autoimmune diseases, including rheumatoid arthritis (RA). Two single nucleotide polymorphisms (SNPs) in the CD40 gene, rs1883832 and rs4810485, are associated with susceptibility to inflammatory and autoimmune diseases and are thought to alter CD40 expression at the mRNA and protein level. This study assessed for the first time the association of these SNPs with RA and CD40 mRNA levels in a western Mexican population. A total of 278 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
(53 reference statements)
1
6
1
Order By: Relevance
“…In the same line, the rs4810485 SNP was associated with CD40 protein expression on CD14 + monocytes and CD19 + B cells from lupus erythematosus patients assessed by flow cytometry [18]. Other studies have reported increased levels of sCD40 in subjects who carry the minor allele of rs1883832 and rs4810485 polymorphisms [25, 32].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In the same line, the rs4810485 SNP was associated with CD40 protein expression on CD14 + monocytes and CD19 + B cells from lupus erythematosus patients assessed by flow cytometry [18]. Other studies have reported increased levels of sCD40 in subjects who carry the minor allele of rs1883832 and rs4810485 polymorphisms [25, 32].…”
Section: Discussionmentioning
confidence: 89%
“…The SNP on the CD40 gene, rs1883832, has been associated with ACS in the presence of the major C allele and has been related with decreased levels of sCD40 in the presence of the minor T allele and risk of cardiovascular diseases [31, 32]. In a western Mexican cohort, this was not identified as a genetic risk factor to rheumatoid arthritis (RA) [25]. This polymorphism has been associated with diminished mRNA expression of CD40 [21, 22]; rs1883832 has been found in high LD with rs4810485, the latter being significantly associated with coronary artery lesion formation in a Taiwanese population [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For −1 C > T SNP, the following primers were used: forward 5'‐CCC CGA TAG GTG GAC CGC GAT TGG T‐3' and reverse 5'‐CCC GCC CTC TGA ACC CCC TAC CAG T‐3'; whereas for 6,048 G > T SNP the primers used were: forward 5'‐TAT TTT TGT AGT TCC TCA TTC TGG A‐3' and reverse 5'‐GCC CCC CTT TAC CTC TTT CCA‐3'. The PCR conditions were as described by Román‐Fernández et al (Román‐Fernández et al, ; Román‐Fernández, Muñoz‐Valle, & Palafox‐Sánchez, ). The amplified 505 bp PCR product containing the −1 C > T SNP was digested with 5 U of Nco I restriction enzyme (New England BioLabs ® ) at 37°C for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…In Mexican population, the CD40 polymorphisms −1 C > T and 6,048 G > T did not found associated with rheumatoid arthritis; however, CD40 mRNA levels were 1.5‐fold higher in RA patients compared with control subjects (Román‐Fernández et al, ). This study aimed to evaluate the association between the −1 C > T and 6,048 G > T genetic variants with disease susceptibility, CD40 mRNA expression, and sCD40 levels in SLE patients.…”
Section: Introductionmentioning
confidence: 99%